PENERAPAN PENDEKATAN OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IV SD NEGERI 37 PEKANBARU - Dwi Hafidah; Gustimal Witri; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The case in this study was the level of the ability of mathematical problem solving of the fourth grade students at 37 primary school Pekanbaru low which the average was 62,3 (unable). This study was conducted based on that case to improve the ability of mathematical problem solving of the fourth grade students at 37 primary school Pekanbaru by using open ended approach. This study was class action research with two cycles on the second semester at year of 2015/2016. After using open ended approach, there was an improvement both on teacher and student’s activity and also the ability of the students on mathematical problem solving. The percentage of the teacher’s activity on cycle I was 80,36% (good) and improved on the cycle II to 87,5% (good). The precentage of the student’s activity on cycle I was 80,36% (good) and improved on the cycle II to 87,5% (good). The average of the ability of mathematical problem solving of the students from their basic score to cycle I improved 15,12 with percentage 24,27%, while to cycle II improved 18,66 with percentage 30%. So, it can be concluded that learning process by using open ended approach can improve the ability of mathematical problem solving of the fourth grade students at 37 primary school Pekanbaru.Keywords: Open ended approach, the ability of mathematical problem solving